Legal Protection and Access to Justice for Sexual Violence Victims with Mental Disabilities in Indonesia - Aulia Putri; Nadia Paramita; Rika Nur'Aini; Yahya Sayyaf (Universitas Negeri Surabaya, 2026)
Legal protection for people with mental disabilities who are victims of sexual violence in Indonesia continues to face complex challenges. Although Law provides a clear legal framework, its implementation has not fully ensured equal access to justice for this group. This study aims to identify structural, normative, and social issues arising in practice, while also evaluating the effectiveness of existing legal protections. The research employs a normative legal method using legislative and conceptual approaches, supported by qualitative analysis of primary and secondary legal materials. The findings reveal a significant gap between legal norms and their implementation. Key issues include judicial procedures that are not disability-friendly, limited access to legal aid, and the lack of appropriate accommodations for victims’ mental conditions. Furthermore, persistent social stigma and the limited capacity of law enforcement officials further weaken the protection provided. Consequently, existing legal protection remains ineffective, both substantively and procedurally. This study proposes an integrative approach through regulatory harmonization, capacity building for law enforcement officials, and the development of inclusive and responsive judicial mechanisms to enhance legal protection and improve access to justice.